Experimental study on relative displacement responses of bridge frames subjected to spatially varying ground motion and its mitigation using superelastic SMA restrainers. Issue 109 (June 2018) - Shrestha, Bipin; He, Li-Xiang; Hao, Hong; Bi, Kaiming; Ren, Wei-Xin
Abstract: Contemporary bridge codes recommend adjusting the fundamental frequencies of adjacent segments close to each other to mitigate relative displacement induced damages arising during the strong seismic events. Previous studies revealed that such recommendation leads to effective mitigation of damages on the bridge structures subjected to uniform ground motions. However, in an elongated bridge structure spatial variations of earthquake ground motions at different supports are inevitable which can result in larger relative displacements. This study presents experimental results from a large-scale (1/6) shake table testing of bridge models with two bridge frames having a total length of 16.67 m, subjected to spatially varying ground motions. Experiments were also carried out with bridge model with superelastic Shape Memory Alloy (SMA) restrainers to evaluate its effectiveness on mitigating bridge responses. It is revealed that even the adjacent bridge frames with fundamental frequencies close to each other are susceptible to the localized damages at the joints due to poundings, which could lead to delayed access to the affected sites after an earthquake. Superelastic SMA restrainers could effectively reduce the opening relative displacement and pounding intensity. Moreover, owing to its superelastic behaviour the restrainers would not require replacement even after strong seismic events. Finally, numerical models of the bridge were developed and parametric studies were performed to comprehend the results of the experiment. Highlights: Result from large-scale shake table experiments are presented. Influence of spatially varying earthquake ground motions evaluated. Effectiveness of SMA restrainers on relative displacement response are evaluated. Mechanisms associated with pounding are discussed and experimentally demonstrated.